Microbial response under sulfate stress in a sulfur-based autotrophic denitrification system - Chen, Yiqiang; Jiang, Xu; Zhao, Juanjuan; Yang, Maosheng; Chen, Yong; Ling, Hong; Liu, Yang; Deng, Feng; Wang, Zhu (Frontiers in Microbiology, 2025)
This study investigated the responses of the bacterial community structure and metabolic pathways in a sulfur-based autotrophic denitrification filter (SADF) system to fast elevated sulfate salinity, from 0.04 to 1.2% in 30 days. Results showed that the SADF system exhibited robust sulfate salinity stress tolerance at low nitrate concentrations. In the context of sulfate scenarios, the genus Thiobacillus significantly proliferated and was identified as the dominant sulfur-oxidizing player in the SADF system, achieving a relative abundance of 63.79% under 1.2% sulfate salinity. Cooperative and competitive interactions were found in the SADF-related microorganisms, promoting stable denitrification performance under high salinity. Surprisingly, with a low hydraulic retention time (HRT) of 60 min, metagenomic sequencing revealed a upregulated abundance of functional genes encoding for enzymes associated with nitrogen and sulfur metabolism, while positive correlations were observed between these two pathways in response to sulfate salinity. Furthermore, global wastewater treatment plants were thoroughly explored for the distribution of the SADF-related microorganisms identified in this study. Interestingly, one-way ANOVA analysis showed that the SADF-related microorganisms were widely distributed globally, demonstrating their universality in potential engineering applications worldwide.